(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: - Archforms play an important role in orthodontic diagnosis and treatment planning. Limitations for tooth movement, especially for incisor retraction arise from the basal bone where teeth are rooted. If teeth move excessively over the alveolar bone, periodontal complications and unstable treatment effects, even the tooth exfoliation may occur. The aim of this study is to compare the maxillary and mandibular arch forms of class I, class II, class III patients reporting for treatment in Saveetha dental college and hospitals, Chennai, Tamil nadu from June 2019 to January 2021.Materials and method: - It is a single centered retrospective study conducted in a private dental institution, Chennai. The data of patients reporting was collected from the dental hospital management system and the arch form was compared. Ethical clearance for this study was obtained from the Institutional review board. Statistical analysis was obtained using SPSS version 20.Results:-The results showed that there is no significant correlation in maxillary and mandibular arch forms among Angle’s Class I, Class II, and Class III malocclusion. Class I occlusal relationship was the most common class of malocclusion followed by Class II malocclusion. Ovoid arch was more common in class I, Class II, Class III malocclusion. Conclusion: - Within the study limits, it was concluded that Class I occlusal relationship was the most common class of malocclusion followed by Class II. Ovoid arch was more common in class I, Class II, Class III malocclusion followed by v-shaped and square arch forms in class I and class III and V-shaped arch was more prominent in class II patients.